1987
DOI: 10.1136/ard.46.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary disease in polymyositis/dermatomyositis: a clinicopathological analysis of 65 autopsy cases.

Abstract: SUMMARY The clinical and autopsy records of 65 patients with either polymositis (24) or dermatomyositis (41) and pulmonary disease were reviewed. Pulmonary symptoms were recorded in 43 of the cases and included dyspnoea in 31, cough in 23, and chest pain in six. Interstitial lung disease was noted at autopsy in 27 patients; almost half of these had arthritis. Bronchopneumonia was found in 35 patients, 31 of these had received prednisone. Dysphagia was present in a similar proportion of patients with and withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
69
2
5

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(79 citation statements)
references
References 19 publications
3
69
2
5
Order By: Relevance
“…Cellular interstitial pneumonia was also described [24], and may also well correspond to NSIP. A recent study by DOUGLAS et al [1] of 22 patients with DPM who underwent surgical lung biopsy concluded that the interstitial lung disease associated with DPM was characterised by a pathological NSIP pattern in 82% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cellular interstitial pneumonia was also described [24], and may also well correspond to NSIP. A recent study by DOUGLAS et al [1] of 22 patients with DPM who underwent surgical lung biopsy concluded that the interstitial lung disease associated with DPM was characterised by a pathological NSIP pattern in 82% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Early reports of the interstitial lung disease associated with DPM suggested similarities with idiopathic pulmonary fibrosis [3][4][5]24], but it is likely that some of these cases may actually correspond to fibrosing NSIP, according to the current pathological criteria. Cellular interstitial pneumonia was also described [24], and may also well correspond to NSIP.…”
Section: Discussionmentioning
confidence: 99%
“…ILD, which develops in 23.1-65.0% of PM/DM patients [116,[118][119][120], is a major cause of death in this disease [116,119,[121][122][123]. ILD leads to life-threatening complications, such as ventilatory failure, secondary pulmonary arterial hypertension and cor pulmonale [116,117,121,122,[124][125][126][127], so the early detection of ILD is a high priority in PM/DM patients. However, in PM/DM patients a careful search for underlying malignancies is strongly advocated.…”
Section: Polymyositis/dermatomyositismentioning
confidence: 99%
“…Pulmonary involvement in PM/DM may precede muscle and skin manifestations and includes respiratory muscle weakness, aspiration pneumonia, ILD, ventilatory insufficiency, infections and drug-induced pneumonia [114][115][116][117]. ILD, which develops in 23.1-65.0% of PM/DM patients [116,[118][119][120], is a major cause of death in this disease [116,119,[121][122][123]. ILD leads to life-threatening complications, such as ventilatory failure, secondary pulmonary arterial hypertension and cor pulmonale [116,117,121,122,[124][125][126][127], so the early detection of ILD is a high priority in PM/DM patients.…”
Section: Polymyositis/dermatomyositismentioning
confidence: 99%
“…6,7 Among the extramuscular manifestations of polymyositis, pulmonary involvement is the most common. 3,10,11 On the other hand, complications of the central nervous system (CNS) are rarely reported. 12 …”
mentioning
confidence: 99%